EU-Japan relations, 1970-2012 : from confrontation to global partnership - Keck, Jörn.; Vanoverbeke, Dimitri.; Waldenberger, Franz. (Routledge contemporary Japan series, 2013)
"This book presents a comprehensive overview of EU-Japan relations from 1970 to the present. It charts developments over the period, analyses key specific areas of importance to the relationship, and concludes by assessing how the relationship is likely to develop going forward. Throughout, the book discusses the factors on both sides which motivate the relationship, including Japan's concern to secure markets for its advanced industrial products, and the factors motivating current negotiations for a deeper and more comprehensive economic and cooperative partnership"--